2015
DOI: 10.1002/hrm.21663
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ Work Experience, Ambidexterity, and Performance: The Contingency Role of the Work Context

Abstract: Scholars have suggested that we need a better understanding about the drivers and performance implications of managers’ ambidexterity. By building a human resource management perspective on managers’ ambidexterity, this article not only examines organizational and functional tenure as important antecedents, but also provides novel insights into the contextual conditions under which the ambidextrous behavior of managers contributes to individual performance. Based on survey research among managers of two large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(188 citation statements)
references
References 131 publications
(243 reference statements)
3
179
0
6
Order By: Relevance
“…In large global firms, positions are defined as job roles, and managers accordingly behave in ways that are consistent with the way their roles are defined (Kahn et al 1964) and shaped by function-specific experience (Mom et al 2015). However, TMT members span boundaries and draw on a wide range of different perspectives due to a vast number of internal and external relations (Collins and Clark 2003;Geletkanycz and Hambrick 1997;Yoo et al 2009).…”
Section: Tmt Boundary-spanning and Mms' Role Conflictmentioning
confidence: 99%
“…In large global firms, positions are defined as job roles, and managers accordingly behave in ways that are consistent with the way their roles are defined (Kahn et al 1964) and shaped by function-specific experience (Mom et al 2015). However, TMT members span boundaries and draw on a wide range of different perspectives due to a vast number of internal and external relations (Collins and Clark 2003;Geletkanycz and Hambrick 1997;Yoo et al 2009).…”
Section: Tmt Boundary-spanning and Mms' Role Conflictmentioning
confidence: 99%
“…Transformational leaders might communicate an opening vision, concentrating on experimentation and developing breakthrough innovations, or they might communicate a closing vision, seeking to attain specific and clear-cut objectives (Zacher and Rosing 2015). Nevertheless, ambidextrous leaders engage in complex cognitive processes (Mom et al 2015) such as integrative or paradoxical thinking (Martin 2007;Smith and Tushman 2005) to accommodate the tensions that are likely to come out when pursuing a sort of diverse opportunities, goals, and needs. They may conflict as for time horizon (O'Reilly 3rd and Tushman 2004), risk profile (March 1991), link to the present strategy (Probst et al 2011;Andriopoulos and Lewis 2009), and leader's responsibilities (Floyd and Lane 2000).…”
Section: Ambidextrous Leadershipmentioning
confidence: 99%
“…Transformational leaders might communicate an opening vision, concentrating on experimentation and developing breakthrough innovations, or they might communicate a closing vision, seeking to attain specific and clear-cut objectives (Zacher and Rosing 2015). Nevertheless, ambidextrous leaders engage in complex cognitive processes (Mom et al 2015) …”
mentioning
confidence: 99%
“…Focusing on the relationship between organizational ambidexterity and performance; although some researchers have shown that organizational ambidexterity directly affects performance (for example, Gibson and Birkinshaw, 2004;Lubatkin et al, 2006), others have identified this relationship as being contingent (Lin et al, 2007;Cao, Gedajlovic and Zhang, 2009;Mom, Fourné and Jansen, 2015), and there are even studies which have found negative effects (He and Wong, 2004;Atuahene-Gima, 2005;Lavie, Kang and Rosenkopf, 2011), and there are even studies that show an inverted U shaped relationship between ambidexterity and performance (Caspin-Wagner, Ellis and Tishler, 2012;Wei, Zhao and Zhang, 2014). Thus, the question as to whether or not -and in which conditions-ambidexterity leads to improved performance is still scarcely developed and even contradictory results exist.…”
Section: Hypothesis 2 Human Resource Flexibility Is Positively Relatmentioning
confidence: 99%